Stress and the Well-being of Nurses: an Investigation using the Demands-Resources- Individual Effects (DRIVE) model and the Well-being Process Questionnaire (WPQ). - Williams, Gary; Pendlebury, Hannah; Smith, Andrew (Advances in Social Sciences Research Journal, 2021)
Previous research shows that nurses have high levels of stress, but less is known about their well-being. The present research used an adapted version of the Demands-Resources-Individual Effects (DRIVE) model to investigate these areas. The Well-Being Process Questionnaire (WPQ), which consists of single items derived from longer scales, was also used. One hundred and seventy-seven British nurses (160 female, 17 male) participated in an online survey. The results showed that work characteristics could be grouped into three factors (resources; demands; and role/change/bullying), as were personality scores (positive personality; openness, agreeable, conscientious; and extraversion, emotional stability). Coping (positive and negative coping) and outcomes (positive and negative outcomes, and positive and negative job appraisals) had a two-factor solution. Results from logistic regressions showed that well-being outcomes were predicted by high positive personality and low negative coping. Positive job appraisals were predicted by high resources and low demands. These findings confirm that the use of the DRIVE model and a single short item measuring instrument can quickly provide information about factors predicting the well-being of nurses.